Direct compression of 170-fs 50-cycle pulses down to 1.5 cycles with 70% transmission - Jeong, Young-Gyun; Piccoli, Riccardo; Ferachou, Denis; Cardin, Vincent; Chini, Michael; Hadrich, Steffen; Limpert, Jens; Morandotti, Roberto; Legare, Francois; Schmidt, Bruno E.; Razzari, Luca (Scientific Reports, 2018)
We present a straightforward route for extreme pulse compression, which relies on moderately driving self-phase modulation (SPM) over an extended propagation distance. This avoids that other detrimental nonlinear mechanisms take over and deteriorate the SPM process. The long propagation is obtained by means of a hollow-core fiber (HCF), up to 6 m in length. This concept is potentially scalable to TW pulse peak powers at kW average power level. As a proof of concept, we demonstrate 33-fold pulse compression of a 1 mJ, 6 kHz, 170 fs Yb laser down to 5.1 fs (1.5 cycles at 1030 nm), by employing a single HCF and subsequent chirped mirrors with an overall transmission of 70%.
CRIS-Team Scopus Importer:2023-04-20